Os gêneros do discursivos no processo de ensino e a aprendizagem da leitura: um olhar a partir do referencial teórico Bakthiniano - Reis , Gilmar de Paiva (2022)
The present study aims to investigate the discursive genres in the teaching and learning process considering the Bakthinian propositions. The study of discursive genres is covered from a dialogic-enunciative perspective, mainly considering the teaching of reading. The concept of discursive genres is analyzed through Bakhtin's contributions, and the way in which multiple discursive genres can be used in the classroom today in view of the paradigm of active responsive understanding of teaching. The dissertation has a textual architecture based on the arrangement of two bibliographic research articles that point out the concept of discursive genre from Bakhtin's perspective, the way in which it is possible to work genres in the classroom, this research points out how the dynamics can be guided between students and teachers considering the integration of culture and life. The objective is to specify how pedagogical narratives approach life by providing a teaching guided by multiliteracies with the use of language present in society and that provide the realization of a lively, dynamic, active and responsible teaching. The results point to the need to broaden the discussion on the subject, in view of the recent educational changes promoted by restrictive educational policies in relation to teacher autonomy, a contradictory factor to the Bakthinian assumptions. Nevertheless, it is concluded to encourage the practice of teaching active responsive reading, as a means of providing the training of individuals who can understand the nuances of the discursive genre to which they are aimed.